Some properties of duplication grammars - Mitrana Victor; Rozenberg Grzegorz (1999)
This paper considers context-free variants of duplication grammars. We investigate their generative capacity, their mutual relationship, and their relationship to the context-sensitive duplication grammars. We solve some problems left open in [6], e.g., proving that all regular languages can be generated by nearly all types of context-sensitive duplication grammars. We also consider some decision problems.
Keywords: Természettudományok; Számítás- és információtudomány